INTRUISI LOGIKA PASAR KE DALAM PARTAI POLITIK - Andi Ali Said Akbar (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
Triggers weak performance and the morality of our politicians because of the presence of the business logic in the process of rooting kandidasi and political parties. Money seemed to be a single instrument to raise the party and gained a lot of voters. These frames influence the selection of the sources of political candidates and the quality of the bond with voters. It is also exacerbated by the political